Implementasi Reka Bentuk Seni Bina Rumah Tradisional Melayu dalam Seni Bina Rumah Moden di Selangor, Malaysia. - Alim, Sarinah; Omar, Roshartini (Research in Management of Technology and Business, 2022)
The architectural design of traditional Malay house buildings in modern house architecture is very rarely seen nowadays and the uniqueness of this architecture is increasingly forgotten. The problem of the study is that a society’s customary and cultural identity is being eroded because it is not valued. Therefore, this study was conducted to enhance the customary and cultural identity of the community with traditional Malay architecture. The objective of this study is to identify the characteristics of traditional Malay house architectural design, identify the level of implementation of traditional Malay house architectural design applied to modern house architectural design, and study measures to improve the implementation of artistic design to build traditional Malay houses into modern house architectural designs. The methodology of this study is a qualitative method that uses the interview instrument of five respondents, namely three architects from a contractor’s company and two traditional Malay house owners around the state of Selangor. The results obtained are the traditional features that can be implemented in the modern house there are 5 namely carvings, high pillars, long roofs, wooden walls, and wide openings for natural lighting and ventilation. However, the level of implementation of traditional architecture is reduced due to financial factors but several steps can be taken by architects and homeowners to improve it by introducing traditional architecture with various unique concepts by architects and appointing skilled personnel in implementing traditional architecture in the modern house to be able to carry out construction work in a more orderly manner. This study was conducted to improve the customary identity and culture of this traditional architecture to provide an overview or idea to the contractors and traditional homeowners so that this traditional architecture can be further developed rapidly in its implementation.